Exploring challenges and solutions in applying green human resource management practices for the sustainable workplace in the ready‐made garment industry in Bangladesh. Issue 3 (11th December 2019) - Islam, Md Asadul; Hunt, Abigail; Jantan, Amer Hamzah; Hashim, Haslinda; Chong, Choo Wei
Abstract: The study aimed to explore challenges and solutions in applying green human resource management practices for the sustainable workplace. The field of enquiry is ready‐made garments factories, with the study drawing on qualitative research. The researchers interviewed 12 managers from leading ready‐made garments factories in Dhaka, Bangladesh. The participants interviewed provided rich qualitative data and identified a number of challenges such as a poor level of knowledge, no rules for practicing, a lack of managerial interest and organisational support, high costs of practicing, and high employee turnover as the main challenges in applying green human resource management practices in the factories of the industry. The study also found that strict rules and regulations, monitoring, courses in universities, training programs, and monetary incentives could be effective solutions in applying green human resource management practices in the organisations. This study is amongst the first in academic research to reveal the challenges and solutions in applying green human resource management practices in organisations; therefore, primary data could be useful for academicians and policymakers for further research and subsequent decision‐making.